New species and additional records of the subgenus Termidonia Motschulsky of the genus Zyras Stephens in China (Coleoptera, Staphylinidae, Aleocharinae) - Yan, Zhu-Qi; Li, Li-Zhen (Zootaxa, 2015)
Two new species are described from Yunnan: Zyras (Termidonia) baihuamontis sp. nov., and Z. (T.) nabanensis sp. nov. Additional records of two species of subgenus Termidonia Motschulsky, 1860 are reported. Adults of the four species are illustrated, and identification key is provided for Chinese species.